(untitled) (Bangladesh Journal of Agricultural Research, 2015)
An experiment was conducted at the Seed Laboratory of Regional Agricultural Research Station (RARS), Jamalpur during the period from May to November 2010 to study the effect of thickness of polythene bags on quality of soybean seed during storage. Seven levels of thickness of polythene bags viz. i) 0.02mm, ii) 0.03mm, iii) 0.04mm, iv) 0.05mm, v) 0.06mm, vi) 0.07mm and vii) 0.08mm were include as treatment in the trial. Seed moisture content, germination percentage, vigor and seedling dry matter weight were taken during May to November 2010 at two month intervals. Results showed that during the storage period the lowest seed moisture content and highest germination percentage, vigor index, seedling dry matter weight and field emergence were found for seed stored in 0.08mm thickness polythene bags. The germination of seed at two months after storage ranged between 76% to 95.3% and that was between 0% and 90.7% after six months of storage under ambient room condition. Soybean seed could be stored safely at ambient condition with more than 80% germination for six months by keeping them in polythene bags having thickness between 0.03mm to 0.08mm with 8% seed moisture content. DOI: http://dx.doi.org/10.3329/bjar.v39i4.22550 Bangladesh J. Agril. Res. 39(4): 709-716, December 2014